The spatial distribution of the common dolphin, Delphinus delphis, along the Portuguese mainland coast and their interaction with the purse seine fishery - Brouder, Sarah (2022)
The common dolphin, Delphinus delphis, is the most abundant cetacean species along the Portuguese mainland coast and are faced with many anthropogenic threats. Over the past decade, intense fishing practices have contributed to a decline in the availability of their main prey, the sardine. Furthermore, the high Purse Seine Fishing (PSF) activity has raised concern over the level of by-catch along the coast. The purpose of the study is to (i) investigate the distribution of the common dolphin along the Portuguese mainland coast, and (ii) to estimate the overlap between the PSF effort and the common dolphin’s distribution. The study uses sighting data from 2005-2020 to identify dolphin hotspot areas. In addition, the study analyses changes in their offshore distribution across different time periods. Finally, the study overlaps Automatic Information System data of the PSF with common dolphin distribution data, in order to identify high by-catch risk areas. The outputs of the study identify major common dolphin hotspots along the central and southern Portuguese mainland coast, which coincide with important fishing ports and geographic features. Furthermore, the common dolphin was found to occur significantly further from the coast during from 2013-2016 (p-value < 0.05), which corresponds with a period of particularly low sardine biomass. Finally, the by-catch risk assessment reported high risk areas off the western Algarve, particularly near important fishing grounds. The study highlights the major common dolphin hotspots and potential conflict areas with the PSF. These results can be used by managers to inform conservation measures and for the sustainable management of PSF fleet along the Portuguese mainland coast.